The Effects of Allicin, a Reactive Sulfur Species from Garlic, on a Selection of Mammalian Cell Lines - Martin C. H. Gruhlke; Carole Nicco; Frederic Batteux; Alan J. Slusarenko (MDPI AG, 2016)
Garlic (Allium sativum L.) has been used as a spice and medicinal plant since ancient times. Garlic produces the thiol-reactive defence substance, allicin, upon wounding. The effects of allicin on human lung epithelium carcinoma (A549), mouse fibroblast (3T3), human umbilical vein endothelial cell (HUVEC), human colon carcinoma (HT29) and human breast cancer (MCF7) cell lines were tested. To estimate toxic effects of allicin, we used a standard MTT-test (methylthiazoltetrazolium) for cell viability and 3H-thymidine incorporation for cell proliferation. The glutathione pool was measured using monobromobimane and the formation of reactive species was identified using 2',7'-dichlorofluoresceine-diacetate. The YO-PRO-1 iodide staining procedure was used to estimate apoptosis. Allicin reduced cell viability and cell proliferation in a concentration dependent manner. In the bimane test, it was observed that cells treated with allicin showed reduced fluorescence, suggesting glutathione oxidation. The cell lines tested differed in sensitivity to allicin in regard to viability, cell proliferation and glutathione oxidation. The 3T3 and MCF-7 cells showed a higher proportion of apoptosis compared to the other cell types. These data show that mammalian cell lines differ in their sensitivity and responses to allicin.